The German Poetry of Paul Fleming : Studies in Genre and History - Sperberg-McQueen, Marian R.; Project Muse; Project Muse. (Baltimore, Maryland : Project Muse, 2020)
This study reassesses the poetry of Paul Fleming (1609-1640) in the context of its own literary, historical, and social background. The four chapters focus initially on generic and historical context. The study of selected texts leads to more general considerations of the sources and significance of certain major themes. A number of poems by Fleming and poets contemporary with him uncovered in the twentieth century are evaluated here for the first time. The result is a substantially revised view of Fleming's poetic development. Fleming is shown to have been a more complex and wide-ranging poet than was conventionally thought, one whose debt to Renaissance literary traditions has been underestimated.
Issued as part of book collections on Project MUSE.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Fleming, Paul, -- 1609-1640 -- Criticism and interpretation; Electronic books